1995
DOI: 10.1016/0014-5793(95)01245-2
|View full text |Cite
|
Sign up to set email alerts
|

Binding of vanadium (IV) to the phosphatase calcineurin

Abstract: X-band electron spin resonance spectroscopy was used to study the binding of vanadium (IV), or vanadyl, to the brain serine/threonine phosphatase-2B, caicineurin. Spectra were determined on frozen solutions of vanadyl and caicineurin at pH 7.4 in the presence of 20% (v/v) glycerol. The binding of vanadyl to the enzyme was established, and the data suggested the presence of two classes of sites, the higher affinity class of which contained two binding sites for vanadyl. The calcium-binding B subunit of the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Vanadate ions from NaVO 4 and Na 3 VO 4 have been shown to mediate phosphorylation of tumor suppressor p53 protein (Suzuki, et al 2007). Vanadate compounds were also reported to inhibit protein phosphatases other than tyrosine specific ones (Parra-Diaz, et al 1995, Reiter, et al 2002. Tyrosine de/phosphorylation is a rare event in yeast: there are no true protein tyrosine kinases and just a few phosphatases (Chi, et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Vanadate ions from NaVO 4 and Na 3 VO 4 have been shown to mediate phosphorylation of tumor suppressor p53 protein (Suzuki, et al 2007). Vanadate compounds were also reported to inhibit protein phosphatases other than tyrosine specific ones (Parra-Diaz, et al 1995, Reiter, et al 2002. Tyrosine de/phosphorylation is a rare event in yeast: there are no true protein tyrosine kinases and just a few phosphatases (Chi, et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In rat tissues treated with vanadium complexes, about 90% of vanadium was in vanadyl form (VO 2+ ) [23] . Vanadyl ions bind to many proteins such as ferritins, albumin, transferrin, phosphatase calcineurin [24][25][26][27] , and F 1 -ATPase [28,29] . The affinity for these targets is at about 10 −10 mol/L [30] .…”
Section: Chemical Biologymentioning
confidence: 99%
“…In vivo, vanadium occurs mainly in its V oxidation state, vanadate, but this is rapidly reduced to the IV oxidation state, vanadyl (9). Using electron spin resonance (ESR) spectroscopy, we recently showed that vanadyl binds to CN and the B-subunit and, interestingly, can increase CN activity (10).…”
Section: Introductionmentioning
confidence: 99%